2018
DOI: 10.1637/11672-050917-reg.1
|View full text |Cite
|
Sign up to set email alerts
|

Biosecurity Assessment and Seroprevalence of Respiratory Diseases in Backyard Poultry Flocks Located Close to and Far from Commercial Premises

Abstract: Raising backyard chickens is an ever-growing hobby in the United States. These flocks can be a substrate for respiratory disease amplification and transmission to commercial facilities. Five hundred fifty-four chickens from 41 backyard flocks were sampled in this study. ELISA kits were used to detect antibodies against avian influenza (AI), infectious laryngotracheitis (ILT), Newcastle disease (ND), infectious bronchitis (IB), Ornithobacterium rhinotracheale (ORT), Mycoplasma gallisepticum (MG), and Mycoplasma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
38
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(46 citation statements)
references
References 13 publications
4
38
3
Order By: Relevance
“…The high seroprevalence of NDV in backyard poultry has an implication on the maintenance of the virus and spread of the disease to commercial flocks. The present study recorded a high NDV seroprevalence (71.4%) at flock level, which is consistent with the findings from other authors [11], [12], [13], [14]. The likely reasons for such finding could be the poor biosecurity, introduction of infected birds to existing flocks, lack of vaccination, close relationship with neighboring birds and, unhygienic feeding practices.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The high seroprevalence of NDV in backyard poultry has an implication on the maintenance of the virus and spread of the disease to commercial flocks. The present study recorded a high NDV seroprevalence (71.4%) at flock level, which is consistent with the findings from other authors [11], [12], [13], [14]. The likely reasons for such finding could be the poor biosecurity, introduction of infected birds to existing flocks, lack of vaccination, close relationship with neighboring birds and, unhygienic feeding practices.…”
Section: Discussionsupporting
confidence: 92%
“…Based on the respondents’ data, these aforementioned practices were adequately adhered to, especially amongst farms with history of ND outbreaks. Furthermore, recent studies advocated for better quarantine, management of sick and dead birds, and improved technical efficiency, especially in backyard poultry systems [11], [28]. However, most of the farmers in this study were little informed about the ND and they rarely submitted samples to appropriate centres during disease outbreaks.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In recent years, several studies have focused on urban and backyard poultry flocks in North America [9,14,15,19,21,29] but few have characterized other non-poultry backyard and small-scale livestock owners [20]. In the present study, most respondents utilized their animals’ products for their own consumption but about half sold animal products (eggs and meat), primarily through internet sales or farmers’ markets with sales less than $10,000 a year.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 41 backyard poultry flocks in California demonstrated a high prevalence of antibodies (between 45% and 97%) to avian respiratory pathogens (e.g., infectious bronchitis, Mycoplasma synoviae and M . gallisepticum ), indicating their potential as a reservoir or amplifier for these diseases [29] and spill-over to commercial production systems. Disease outbreaks in commercial operations, such as virulent Newcastle Disease (vND, known as Exotic Newcastle Disease) and Marek’s Disease, have originated in backyard flocks and spread to commercial flocks [3,11].…”
Section: Discussionmentioning
confidence: 99%